Quality of work life on employees job involvement and affective commitment between the public and private sector in Malaysia - P. Yukthamarani Permarupan; Abdullah Al- Mamun; Roselina Ahmad Saufi
This study is designed to examine the relationship between the quality of work life (QWL), employees’ job involvement and affective commitment among the employees of the public and private sector organizations in Malaysia. A total of 334 middle management level employees were selected to participate in this study. QWL was measured with five dimensions which are ‘fair and appropriate salary’, ‘working conditions’, ‘capacities at work’, ‘opportunities at work’ and ‘organization climate’. The intervening and dependent variables are job involvement and affective commitment respectively. The results indicated that working conditions, opportunities at work and climate organization had a relatively higher impact on ‘job involvement’ and ‘affective commitment’. Findings of this study contributed to the knowledge and understanding of the effect of the selected factors, which leads to better understanding among the practice for both public and private organizations in Malaysia towards attainment of a superior level of efficiency to thrive in an ever competitive business world.